2002
DOI: 10.1080/713603089
|View full text |Cite
|
Sign up to set email alerts
|

Cyproterone, norethindrone, medroxyprogesterone and levonorgestrel are less potent local human growth hormone and insulin-like growth factor I secretion stimulators than progesterone in human breast cancer explants expressing the estrogen receptor

Abstract: The aim of the present study was to compare the ability of natural progesterone and synthetic progestins to stimulate local growth hormone (GH) and insulin-like growth factor I (IGF-I) secretion by breast cancer explants. Explants obtained during surgery were divided according to their estrogen/progesterone receptor phenotype - ER(+)PR(-); ER(+)PR(+); ER(-)PR(+) - as determined by immunocytochemistry. Natural progesterone (10(-5) mol/l) and synthetic progestins (cyproterone acetate (5 x 10(-7) mol/l), norethin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The second part of our study confirmed our earlier finding of progesterone-induced increase in IGF-I secretion in malignant and non-malignant breast PR(+) explants [5][6][7]. Additionally, we once again showed the decreased IGFBP-3 level which was paralleled by the increase in IGFBP-2 secretion by hormone-dependent breast cancer explants [6,27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The second part of our study confirmed our earlier finding of progesterone-induced increase in IGF-I secretion in malignant and non-malignant breast PR(+) explants [5][6][7]. Additionally, we once again showed the decreased IGFBP-3 level which was paralleled by the increase in IGFBP-2 secretion by hormone-dependent breast cancer explants [6,27].…”
Section: Discussionsupporting
confidence: 93%
“…We previously reported the stimulatory effect of progesterone on the activation of local hGH/IGF-I/IGF binding protein axis in breast tissue expressing progesterone receptors [5,6]. Moreover, we showed that the differences in secretion of hGH and IGF-I from breast tissue explants depended on the type of progestagens used and the steroid receptor phenotype of both malignant and adjacent non-malignant tissue [7].…”
Section: Introductionmentioning
confidence: 58%
“…While some researchers reported that LNG or LNG-IUS associated with a decreased risk of ovarian and endometrial cancer, without increased risk of breast cancer [7, 10, and 15]. Scientists think that the different role of LNG or LNG-IUS in cancers may be associated with pathological process [12,13], hormone levels [23], or the expression of molecules related hormone [24][25]. For example, Nikolopoulos et al and Westin et al found LNG-IUS offers an effective and safe treatment for early-stage, lowgrade endometrial cancer [12,13]; Siegelmann-Danieli et al think that LNG-IUS was associated with a slightly increased risk for invasive breast cancer in the subgroup of women in their early 40's, while not associated with an increased total risk in perimenopausal women [23].…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that progesterone could induce secretion of these growth factors from human breast cancer explants in-vitro [23]. GH secretion of malignant cell lines was increased in response to progesterone even when progesterone receptors were absent.…”
Section: In-vitro and Animal Datamentioning
confidence: 98%
“…GH secretion of malignant cell lines was increased in response to progesterone even when progesterone receptors were absent. Synthetic progestins showed a variable effect on these growth factors, depending on the type of progestin used, the receptor status of the cell lines, and whether or not the cell lines were malignant [23].…”
Section: In-vitro and Animal Datamentioning
confidence: 99%